Aplikasi edible coating pati garut (Maranta arundinacea) pada apel (Malus sylvestris) potong dengan penambahan jeruk nipis dan daun mint - Faizal Junianto; Harto Widodo; Nanik Suhartatik; Merkuria Karyantina (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
An edible coating is a thin layer of hydrocolloid materials such as polysaccharides, polypeptides, lipids, and composites. Apples are one of the fruits that often undergo minimal processing, such as slicing. Cut apples are susceptible to damage, which can lead to rapid browning, to slow this reaction, an edible coating can be applied. This study aimed to determine the quality of apple slices after being treated with an edible coating made from arrowroot starch with lime juice and mint leaf during storage. This study used a Completely Randomised Design with two factors: storage time (0, 2, 4, and 6 days) and the concentration of lime juice and mint leaf. The results showed that adding lime juice and mint leaf did not significantly affect water content, vitamin C, and weight loss of apple slices, while the longer the storage, the more damaged the sliced apples were. Weight loss, antioxidant activity, total phenols, vitamin C, and total aerobic bacteria decreased during storage. The treatment of adding 13% lime juice and 10% mint leaves was able to suppress the total number of bacteria to 5.77 log 10 CFU / g at a shelf life of 6 days. The treatment of adding mint leaves and lime extract was able to inhibit damage to sliced apples for 6 days of storage